Um bruxo e seu tempo: as obras de Gerald Gardner como expressões contraculturais - Terzetti Filho, Celso Luiz (2012)
This dissertation examines the history of Wicca, a religious system created by Gerald Gardner in England in the late 40th through three of his works that deal specifically with its conception of witchcraft, " High Magic s Aid" (1949) "Witchcraft Today" (1954) and "The Meaning of Witchcraft" (1959). Within a perspective that takes into account your inspirations for the creation of a system resulting from their original religious movement as a seeker in the occult milieu of his time, we seek to understand Wicca as a religious system through a counter cultural interpretation. Thus this work asks in what sense the works of Gardner is a historical product of their social time. Our hypothesis is that his works are a product of the social history of postwar England to the extent that Gardner, in constructing his conception of witchcraft in his works, appropriated counter-trend to compose a countercultural religious system